2018
DOI: 10.1111/hsc.12680
|View full text |Cite
|
Sign up to set email alerts
|

Enablers of psychological well‐being for refugees and asylum seekers living in transitional countries: A systematic review

Abstract: The purpose of this systematic review was to locate and synthesise existing peer-reviewed quantitative and qualitative evidence regarding enablers of psychological well-being among refugees and asylum seekers living in transitional countries and for whom migration status is not final. Systematic searches were conducted in nine databases: Academic Search Premier, CINAHL, Embase, Emcare, Medline, Psychology and Behavioral Science, PsycINFO, Scopus, and Web of Science. Search terms were related to refugees and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 39 publications
(281 reference statements)
5
41
1
2
Order By: Relevance
“…However, the observed positive association between cognitive restructuring and wellbeing may be attributed to this coping strategy's fit with other sources of distress, such as trauma exposure [69]. Moreover, previous research has shown that cognitive strategies such as restructuring and reframing might generate hope for the future and positive feelings of meaning and purpose among refugees and asylum-seekers, despite the difficult aspects of the situation [30]. In summary, cognitive restructuring might be insufficient for coping with post-migratory interpersonal threats and stressors, but still have beneficial effects on the wellbeing of asylum seekers.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…However, the observed positive association between cognitive restructuring and wellbeing may be attributed to this coping strategy's fit with other sources of distress, such as trauma exposure [69]. Moreover, previous research has shown that cognitive strategies such as restructuring and reframing might generate hope for the future and positive feelings of meaning and purpose among refugees and asylum-seekers, despite the difficult aspects of the situation [30]. In summary, cognitive restructuring might be insufficient for coping with post-migratory interpersonal threats and stressors, but still have beneficial effects on the wellbeing of asylum seekers.…”
Section: Discussionmentioning
confidence: 95%
“…Yet, several coping strategies have been identified to date in adult refugees and asylum seekers that might assist in dealing with post-migration stressors and promote mental well-being. Social support, defined as interactions with family members, friends, peers, and professionals for information, affirmation or understanding [29], is one of the most commonly reported coping strategies utilized by refugees and asylum seekers [30]. Reaching out for support provides a sense of social connection and this is done in three ways; either via bonding with family and similar ethnic groups during the early years of resettlement [25]; or via bridging, defined as connections with other communities to assist in learning the host language and having contacts with the wider society; and thirdly, by linking with larger organizational institutions [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Familial, religious, and ethnic group support has been shown to buffer against poor mental health and enhance wellbeing in African refugees residing in countries of first asylum, as well as those resettled in high-income countries (Abraham et al 2018;Campbell 2006;Gladden 2012;Posselt et al 2018;Schweitzer et al 2006Schweitzer et al , 2007, including in older adult refugees groups (Lamba and Krahn 2003;Silveira and Allebeck 2001;Mölsä et al 2014). Despite these positive findings, there is a knowledge gap related to the specific range and sources of support utilized by refugees across generations in low-and middleincome countries (LMICs), in which 85% of refugees are hosted globally (UNHCR 2018a).…”
Section: Introductionmentioning
confidence: 99%